Relevansi Pemikiran Hamka Terhadap Pendidikan Islam Masa Kini - Naili, Ilma Zahrotun; Mutrofin, Mutrofin (Pascasarjana IAIN Metro, 2024)
This research discusses the relevance of Hamka's thoughts on Islamic education today. This type of research is qualitative research with library research data collection techniques with data sources coming from manuscripts in the form of documents that are in accordance with the object of research and then analyzed to produce conclusions in accordance with the research objectives. Based on the results of the research, it is concluded that Hamka's Islamic education thinking is still relevant to be applied to today's Islamic education model. This is because Hamka's thoughts related to Islamic education by optimizing all human potential by using Islamic religious principles can be used as a bulwark in the face of rapid technological developments that have the potential to erode human morals and potentially make humans embrace secularism.